Peran Sistem Informasi yang Didukung Teknologi Informasi dalam Optimasi Pengelolaan Keuangan Desa Melalui Workshop Sistem Informasi Keuangan Desa (Sikades): (Studi pada Aparatur Desa Se-Kabupaten Indragiri Hilir) - Anwar, Misbahul; Patolo, Suryo (Akmenika, 2013)
This study aims to examine the role of the information system supported by informa-tion technology in order to optimize village financial management in Indragiri Local Government. The method of research was conducted by questionaire survey to 100 village governmental officers. Paired sample t-test is used to examine the capability of the officer in financial management before and after the course. The result of the examination show there is capacity improvement in financial management by all the village governmental officers.